The Effect of Domes Geometry Formation on Acoustic Performance in Mosques (Journal of Engineering, 2006)
The research explain The Effect of Domes Geometry Formation (size, shape,..) on AcousticPerformance, that for importance of this element in designing aspect specially in Islamic architectureand in the mosques building.The research follow sound reflection diagrams to obtain graphic forms that explain the affection ofvarious Geometry Formation on Acoustic Performance , after analyze the graphic forms the finalconclusions are introduced to obtain a primary vision about a capability of dome and who deal with it.